City Architecture as the Production of Urban Culture: Semiotics Review for Cultural Studies - Daniel Susilo; Mega Primatama (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2018)
This article aims to describe correlation between city's architecture as urban culture and cultural studies, specifically in semiotics. This article starts from Chris Barker's statement about city and urban as text in his phenomenal book, Cultural Studies, Theory and Practice. City as a complex subject has been transformed as the representation of urban culture. In the post-modernism view, urban culture as cultural space and cultural studies' sites have significantly pointed to became communications discourse and also part of the identity of Semiology. This article uses semiotics of Saussure for the research methods. Surabaya and Jakarta has been chosen for the objects of this article. The result of this article is describing the significant view of architecture science helps the semiotics in cultural studies. In other way, city's architecture becomes the strong identity of urban culture in Jakarta and Surabaya. Architecture approaches the cultural studies to view urban culture, especially in symbol and identity in the post-modernism era.